Dynamics of Intraprocedural Dominant Frequency Identifies Ablation Outcome in Persistent Atrial Fibrillation - Pithon, Alain; McCann, Anna; Buttu, Andréa; Vesin, Jean-Marc; Pascale, Patrizio; Le Bloa, Mathieu; Herrera, Claudia; Park, Chan-Il; Roten, Laurent; Kühne, Michael; Spies, Florian; Knecht, Sven; et al. (Frontiers in Physiology, 2021)
Background: The role of dominant frequency (DF) to track the efficiency of stepwise catheter ablation (step-CA) in persistent atrial fibrillation (peAF) remains poorly studied. We hypothesized that the DF time-course during step-CA displays divergent patterns between patients in whom step-CA successfully restores long-term sinus rhythm (SR) and those with recurrence. Methods: Forty consecutive patients underwent step-CA for peAF (sustained duration 19±11 months). DF was computed on electrograms recorded from the right (RAA) and left (LAA) atrial appendages, and the coronary sinus before and during step-CA synchronously to the 12-lead ECG. DF was defined as the highest peak within the power spectrum. Results: peAF was terminated by step-CA in 28 patients (left-terminated [LT]), whereas 12 patients remaining in AF after ablation (not left-terminated [NLT]) were cardioverted. Over a mean follow-up of 34±14 months, all NLT patients had a recurrence. Of the 28 LT patients, 20 had a recurrence, while 8 remained in SR throughout follow-up. RAA and V1 DF had the best predictive values of procedural failure to terminate AF (area under the curve 0.84, p<0.05). A decision tree model including a decrease in LAA DF ≥6.61% during the first 20-min following pulmonary vein isolation (PVI) and a baseline RAA DF <5.6 Hz predicted long-term SR restoration with a sensitivity of 83% and a specificity of 93% (p<0.05). Conclusion: High baseline DF values are predictive of unfavorable ablation outcomes. Reduction of the LAA DF at early ablation steps following PVI is associated with procedural AF termination and long-term SR maintenance.